Positive Solutions to a Second-Order Discrete Boundary Value Problem - Xiaojie Lin; Wenbin Liu (Discrete Dynamics in Nature and Society)
We are concerned with second-order discrete boundary value problems and obtain some sufficient conditions for the existence of at least one positive solution by using the fixed point theorem due to Krasnosel'skii on a cone.